Tradisi Puasa Asyura di Pondok Pesantren KH Ahmad Dahlan Kuantan Singingi - Atik devi kusuma; Elvita sarah azzahra; Salsa bila khotrun nada; Wardah yuni kartika; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2023)
This study starts from understanding the hadith regarding the recommendation to fast Ashura (9, 10, 11, every month of Muharram). This study looks at the history of the practice and implementation of the Ashura fast and finds out how the students and administrators in the KH Ahmad Dahlan Islamic Boarding School environment interpret the implementation of the Ashura fast. This research is descriptive in nature, namely systematically explaining the livelihood of hadith at the KH Ahmad Dahlan Kuantan Singingi Islamic Boarding School. The approach used in this research is a phenomenological approach. This research concludes that the first thing is to carry out the Ashura fasting tradition carried out by students of the KH Ahmad Dahlan Kuantan Singingi Islamic Boarding School which was founded in 1992. Before breaking the fast, the KH Ahmad Dahlan Kuantan Singingi Islamic Boarding School administrators held an iftar in the Nurul Ilmi mosque, followed by Maghrib prayers and Isha congregation. Second, the activity of fasting Ashura is a proof of love for the Prophet, namely by observing his Sunnah. Because the Sunnah is not only known, but practiced. Apart from that, it is also a way to increase solidarity between students.